BFGF binding cardiac extracellular matrix promotes the repair potential of bone marrow mesenchymal stem cells in a rabbit model for acute myocardial infarction. (14th December 2015) - Zhang, Guang-Wei; Gu, Tian-Xiang; Guan, Xiao-Yu; Sun, Xue-Jun; Qi, Xun; Li, Xue-Yuan; Wang, Xiao-Bing; Yu, Lei; Jiang, Da-Qing; Tang, Rui; Li-Ling, Jesse
Abstract: To assess the effect of basic fibroblast growth factor-binding extracellular matrix (bFGF-ECM) combined with bone marrow mesenchymal stem cells (BMSCs) transplantation on acute myocardial infarction (AMI) and explore the underlying mechenisms. Rabbit hearts were processed by decellularization with sodium dodecyl sulfate (SDS) perfusion, heparin immobilization, bFGF-binding and homogenization, for preparation of bFGF-binding cardiac ECM suspension (bFGF-ECM). Thereafter, the characteristics of bFGF release were analyzed in vitro . Following ligation of the mid-third of the left anterior descending artery, the rabbits were divided into a control group (no treatment), BMSCs group (BMSCs transplantation), bFGF-ECM group (bFGF-ECM implantation), and BMSCs  +  bFGF-ECM group (BMSCs and bFGF-ECM implantation). Apoptosis and differentiation of implanted BMSCs, and the left ventricular (LV) remodeling and function were assessed. The ex vivo proliferation, apoptosis, migration and differentiation of BMSCs were determined after exposure to bFGF and/or ECM. The ECM could sustainably release bFGF. 24 h and 6 weeks after the operation, improved viability and differentiation of the implanted BMSCs, as well as inhibited dilatation and preserved function of the left ventricle (LV), were significant in the BMSCs  +  bFGF-ECM group compared with other groups ( P   <  0.05), although BMSCs and ECM-bFGF groups also showed better results than control group ( P   <  0.05). Additionally, ECM and bFGF showed a synergistic effect on BMSCs proliferation, viability, migration and differentiation. The combination of bFGF-binding ECM and BMSCs implantation may promote myocardial regeneration and LV function, and become a new strategy for the treatment of AMI.